A prospective study to evaluate the etiologies and parameters of voice assessment in patients of vocal cord paralysis - Joshi, Anagha A.; Singh, Vijaykumar; Rajani, Sana Zehra N. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Evaluation of voice disorders are performed using multiple approaches but there is no single standard method. Our study compared the various voice assessment measures and their clinical relevance for unilateral vocal cord palsy (uVCP). Methods: 30 patients of uVCP were assessed and followed up on day 15, 30 and 90 of diagnosis. At each visit, perceptual analysis of voice, grade (G), rigid 700 Hopkins laryngoscopy to measure the phonatory gap (PG), maximum phonation time (MPT), and voice handicap index (VHI) were noted. Results: The results were analysed in two ways, one on the basis of improvement in VHI and the other on the basis of PG. When two groups (‘improved group 1’ and ‘unimproved group 1’) were formed and compared on the basis of VHI; MPT, Grade and ‘change in PG’ of the improved group showed a significant difference as compared to the unimproved group. Whereas when two groups (‘improved group 2’ and ‘unimproved group 2’) were formed and compared on the basis of improvement in PG, none of the parameters of the improved group showed a significant difference as compared to the unimproved group. Conclusions: All parameters correlate well with VHI than with PG, hence VHI alone can be sufficient to assess the improvement in voice. Although rigid laryngoscopy is essential initially for diagnosis, it need not be necessary to for further evaluation for improvement in voice.